Nonspecific pain in the lumbosacral area: clinical features of and approachesto drug therapy (according to the materials of the European guidelinesfor the management of nonspecific lumbosacral pain) - Tat'yana Alekseevna Raskina; M V Koroleva; Tatyana Alekseyevna Raskina; M V Koroleva (Современная ревматология)
The paper describes the .specific features of the clinical presentation, diagnosis, and treatment of pain syndrome in the lumbosacral area.